‘Headed Home’: Glissant, Bhabha and the politics of homecoming in Walcott’s Omeros and The Odyssey / Haleh Zargarzadeh - Haleh, Zargarzadeh (2015)
This thesis examines representations of home and homecoming in Derek Walcott’s Omeros (1990) and The Odyssey: A Stage Version (1993). The quest for home and at-homeness has been identified as a primary motif in contemporary literature in English. Within conventional scholarship, home or “nostos,” homecoming, is usually associated with genealogy and geography; it is also traditionally defined in terms of homogeneity. In this study, I demonstrate how the postcolonial imaginings of Walcott’s Homeric-inspired texts dismantle such fixed and unitary understandings of home. I show how these works reject notions of linearity and purity to construct a model of home and homecoming that recognizes and affirms multiplicity and displacement. This postcolonial paradigm of home, I argue, is more attuned to the realities of diaspora, the specificities of Caribbean identity, and the distinctive contours of its colonial history and experience. Toward this end, the study’s four chapters examine the concept of home and homecoming from various perspectives, each framed and informed by Édouard Glissant’s theoretical notions of “opacity,” “relation,” “creolization,” “detour,” and “verbal delirium,” and Homi Bhabha’s concept of the “unhomely.” In reading the trope of “nostos” through these postcolonial concepts, this study moves away from a purely classicist approach to argue that home, for Walcott, invokes both the pleasures of familiarity and the terrors and ambivalences of unhomeliness.